Evaluation of an acoustic telemetry transmitter designed to identify predation events. Issue 9 (23rd March 2017) - Halfyard, Edmund A.; Webber, D.; Del Papa, J.; Leadley, T.; Kessel, S. T.; Colborne, S. F.; Fisk, A. T.
Summary: The field of acoustic telemetry has evolved rapidly and now permits the remote sensing of animal behaviour, movement, physiology and survival in environments, and species not previously possible. However, an inability to detect when a telemetered animal is consumed by a predator can complicate accurate interpretation of the telemetry data. In this paper, we describe the efforts taken to test the two generations of a novel prototype acoustic telemetry transmitter designed specifically to detect predation. Testing involved either staged predation events where tagged prey (Rainbow Trout Oncorhynchus mykiss and Yellow Perch Perca flavescens ) were fed to captive Largemouth Bass Micropterus salmoides, or false‐positive testing where prey fish were tagged and held without the risk of predation. Metrics of interest were (i) the rate of correctly identifying the predation events, (ii) signal lag (i.e. the time required to detect a predation event), (iii) tag retention time in the predator's gut, and (iv) the rate of false‐positive triggering in both live and dead prey fishes. Staged predation events were successfully identified in 61/65 and 52/55 trials for generation 1 and 2 tags, respectively. Signal lag time was reduced in generation 1 tags (generally between 1 and 9 h) relative to generation 2 (3–29 h); although signal lag was highly variable. A generalized linear mixed model (GLMM) indicated strong evidence that signal lag and tag retention were both negatively correlated with water temperature, but were not affected by prey species and only slightly by individual predator traits. There was preliminary evidence that prey size may be an important determinant of both signal lag and tag retention. False‐positives in live fish were absent after 120 days for generation 1 tags ( n = 31), however, the false‐positive rates were significantly higher (10/44) after only 66 days for generation 2 tags. False‐positives in dead fish showed that 20% of the generation 2 predation tags would falsely trigger 2–3 days post‐mortem. Testing of the novel predation tags was encouraging, however, further testing is recommended. Predation tags will be an important contribution to the field of acoustic telemetry, thus, permitting the improved data interpretation and less‐subjective estimates of predation rates in biotelemetry studies.